1975
DOI: 10.7326/0003-4819-83-4-489
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Sexual Behavior in the Spread of Hepatitis B Infection

Abstract: There is a significant excess of serologic evidence of hepatitis type B infection in two high-promiscuity populations: patients with venereal diseases and their unrelated sexual contacts (15% to 18%) and male, but not female, homosexuals (37% to 51%). Spouses of asymptomatic chronic carriers of antigen had a higher prevalence (26% to 28%) than spouses of noncarriers (10% to 11%); however, the prevalence in the former is relatively low when compared with rates seen in other relatives of carriers. Persons who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
0
5

Year Published

1977
1977
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(72 citation statements)
references
References 24 publications
6
61
0
5
Order By: Relevance
“…In Inverclyde, in 87% of 92 cases reporting injecting drug use, 3% were infected through heterosexual contact with a case [21]. Our results are also consistent with the findings of previous studies in non-outbreak settings, where multiple partners, duration of sexual activity, or history of another sexually transmitted infection have been associated with an increased risk of HBV transmission [22][23][24][25]. MSM are a group with a higher prevalence of HBV than the general population.…”
Section: Discussionsupporting
confidence: 82%
“…In Inverclyde, in 87% of 92 cases reporting injecting drug use, 3% were infected through heterosexual contact with a case [21]. Our results are also consistent with the findings of previous studies in non-outbreak settings, where multiple partners, duration of sexual activity, or history of another sexually transmitted infection have been associated with an increased risk of HBV transmission [22][23][24][25]. MSM are a group with a higher prevalence of HBV than the general population.…”
Section: Discussionsupporting
confidence: 82%
“…The prevalence of infection increased significantly by age and risk behavior, corroborating findings that sexual behavior is the predominant mode of HBV transmission among MSM. [18][19][20][21][22] As reported for the general population, rates of HBV infection were higher for MSM of Asian, Black, or mixed race than for White MSM. 26 As we expected, young MSM who used a regular source of health care were more likely to have been immunized than those who did not have a regular source of health care or did not use health care services.…”
Section: Discussionmentioning
confidence: 61%
“…From these, we constructed a risk hierarchy (low, moderate, high) based on factors known to be associated with HBV infection among MSM. [18][19][20][21][22] We defined low risk as having never engaged in anal sex and having 5 or fewer lifetime male sex partners. High risk was defined as having ever engaged in anal sex and meeting 1 or more of the following criteria: having had 20 or more male sex partners; having ever exchanged sex for money, food, or drugs; having, or having had, a STD; having ever engaged in anal fisting; and having ever shared needles or equipment to inject drugs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among nonretarded, however, the importance of sexual transmission of hepatitis B has been particularly emphasized in male but not female homosexuals. 3 However, a literature review regarding the potential for this mode of institutional spread yielded conflicting results. One study of a heterogenous g r o u p of institutionalized retardates reported a 14.5% incidence of homosexual behavior.…”
Section: Homosexuality In Institutionalized Retardatesmentioning
confidence: 99%